Implementation of Participatory Community Tourism Development Model - Muhammad Amin Wattimena; Herman Surijadi; Muhamad Amin; Muhammad Nur Deny Musa; Rahma Satya Masna Hatuwe (Journal of Business Application, 2024)
The study aims to analyze community-based tourism development at Pantai Kuako, Maluku. It seeks to enhance community engagement, identify local potentials, promote cultural richness, and increase environmental awareness. Additionally, it aims to boost tourist visits, local income, and community participation in tourism development programs. This research employs a qualitative descriptive method to comprehend individuals' experiences in community-based tourism development at Pantai Kuako. Data are gathered from both secondary and primary sources, including government policy documents and Focus Group Discussions (FGDs) involving 20 skilled informants. Data analysis follows Miles and Huberman's (2014) approach, involving data reduction, data presentation, and conclusion drawing. The analysis findings emphasize the significance of Community-Based Tourism (CBT) in fostering sustainable and inclusive tourism development. CBT strengthens the local economy, empowers communities, preserves culture, and promotes environmental responsibility. At Pantai Kuako, tourism development progresses through initial, intermediate, and advanced stages, with tailored strategies for each stage.